Backbarrier evolution at a medium-term scale - Carrasco, Ana Rita (2017)
This study reports the medium-term evolution of a sandy backbarrier and its relation with prevailing wind conditions. Obtained results demonstrated that Ancão backbarrier does not behave as a scale-down version of higher energy fetch-limited or oceanic beaches, being considered as a low-energy beach with extremely low wind-induced wave conditions. Volumetric changes during the three years monitoring were small, and the analysis of low-scale changes was divided into four beach compartment: upper beach, beach face, tidal flat, sand bank. There was no significant correlation between prevailing wind conditions, volume and grain-size variation, neither a marked seasonal pattern. Some wind-induced beach changes were perceptive in the grain size variations, related mostly to aeolian offshore sediment transport. Morphological changes were similar in the upper part of the profile, including upper beach and beach face, with changes mostly related to wind and windwaves energy. The lower part of the profile, which includes the tidal flat and the sand bank, frequently react independently from the upper part of the profile, although, sediment exchange between them was noticed during extreme conditions. The lower part of the profile had larger volumetric variability, without any evident wind dominance. The studied beach revealed high morphologic resilience, yet the overall quantities of sediment transported between 2005 and 2008 has particular relevance in the local coastal management context. Further research is needed to develop a broad-scale model of fetch-limited beaches, including the less energetic settings of the spectra such as backbarrier environments.